Long-term complete response with third-line PARP inhibitor after immunotherapy in a patient with triple-negative breast cancer: a case report - Caputo, Roberta; Pagliuca, Martina; Pensabene, Matilde; Parola, Sara; De Laurentiis, Michelino (Frontiers in Oncology, 2023)
While standard treatment has shown efficacy in patients with Breast Cancer genes (BRCA) mutations, recurrence rates are high and additional effective therapies are needed. Olaparib, a poly adenosine diphosphate-ribose polymerase (PARP) inhibitor, approved for the treatment of metastatic germline BRCA1/BRCA2 breast cancer (BC), has demonstrated evidence of a progression-free survival (PFS) benefit, good safety profile, and improved quality of life compared with standard chemotherapy. We here describe the case of a patient with BRCA1 mutated advanced BC and a long history of response to chemotherapy and immunotherapy who received systemic treatment with olaparib. First diagnosed in March 2011 at the age of 38 years with early-stage BC of the right breast, she underwent quadrantectomy plus ipsilateral axillary lymphadenectomy and adjuvant treatments with chemotherapy regimen containing 5-fluorouracil, epirubicin and cyclophosphamide (FEC) followed by radiotherapy. Five years later, following a contralateral nodule detection leading to left breast quadrantectomy, she received adjuvant systemic treatment with docetaxel plus cyclophosphamide and radiotherapy. Gene testing showed germline BRCA1 deleterious variant, she underwent bilateral prophylactic mastectomy and oophorectomy. One year later, skin metastasis and bone infiltrations were detecteed, and she was started on first-line systemic treatment. The patient was enrolled in the IMpassion131 trial (investigating atezolizumab addition to paclitaxel) but unblinding showed she was randomized in the placebo arm. She received second-line systemic therapy with LAG525 plus carboplatin (CLAG525B2101 trial) resulting in 14 months PFS. At disease progression, she was eligible for systemic third-line therapy with olaparib (300mg twice daily) and had a complete response after 6 months of therapy and a PFS of 40 months at the time of writing. To the best of our knowledge, this is the first report of a complete response following treatment with third-line systemic olaparib in a long-This is a provisional file, not the final typeset article responding patient and relatively good tolerability and quality of life, pre-treated with both chemotherapy and immunotherapy.